Applying the Theory of Planned Behaviour with the addition of role-identity to predict lecture attendance behaviour - Majudith, Nadira (School of Management Studies, 2020)
This study aimed to investigate the behaviour of lecture attendance amongst undergraduate students at the University of Cape Town (UCT) by applying the Theory of Planned Behaviour (TPB). A total of 169 respondents completed either a hard copy or online survey whilst meeting the inclusion criteria. The sample consisted of students from a first-year mathematics course (which had compulsory lecture attendance for registered students) and from a first-year organisational psychology course (which had voluntary lecture attendance for registered students). The study aimed to broaden the limited knowledge which exists around the perceptions of students regarding lecture attendance specifically in a South African context. Confirmatory Factor Analysis, Exploratory Factor Analysis and reliability analyses strongly supported the application of the TPB model scales and role-identity scale. Regression analysis showed that only attitudes help to predict intention towards lecture attendance behaviour where subjective norms, perceived behavioural control and role-identity were not significant predictors. Intentions were also seen to be highly correlated to actual attendance behaviour as well as helping to predict actual attendance behaviour. Actual behavioural control (ABC) was not seen as a moderator between intention and actual lecture attendance. Practical and theoretical implications were discussed. The information generated by this study can be used to further understand the occurrence of, and students’ perceptions of lecture attendance.